Intense, Long‐Duration Geomagnetically Induced Currents (GICs) Caused by Intense Substorm Clusters - Rajkumar Hajra (Space Weather)
Abstract Geomagnetically induced current (GIC) measurements at the Mäntsälä, Finland (57.9° magnetic latitude) gas pipeline from 1999 through 2019 are analyzed. It is found that the GIC events with peak intensity > 10 A are not individual peaks, but occur in clusters with duration from ∼5 to ∼38 hr when GIC values are almost continuously above ∼1.5 A. The intense, long‐duration GIC > 10 A clusters (ILG10) are characterized by average (median) duration of ∼17 ± 9 hr (∼14 hr), peak intensity of ∼21 ± 10 A (∼19 A), and time‐integrated current flows of ∼1.0 ± 0.7 A‐d (∼0.9 A‐d) for all events under study. An one‐to‐one correlation is observed between the ILG10 events and intense substorm clusters characterized by average (median) duration of ∼20 ± 10 hr (∼17 hr), peak westward auroral electrojet intensity (presented by SuperMAG AL or SML index) of ∼− 2,238 ± 843 nT (∼− 2,099 nT) for all events. About 10–60 min fluctuations in the ILG10 events are found to be induced by substorm (SML) activity, and geomagnetic pulsations. A detailed study is presented on the local time, solar cycle, and geomagnetic dependencies of the ILG10 events. This will hopefully augment the predictability of the intense GICs.